PEMANFAATAN LIMBAH SABUT KELAPA MENJADI INOVASI TANAMAN HIAS KOKODAMA - Nelvia Ibrahim (JURNAL PENGABDIAN MANDIRI, 2025)
Kokedama is a unique Japanese planting technique. Plants are grown in moss-covered balls of soil-based planting material. Kokedama can be adjusted by replacing the moss soil wrap with coco fiber, which is normally discarded. In Indonesia, many people, particularly women, enjoy cultivating and collecting decorative plants. Only use traditional planting media, such as plastic or stone pots. Kokedama training is deemed appropriate in today’s society. The goal of this service is to introduce and train new techniques for making attractive plants using the kokedama method